Ethnobotanical study of medicinal plants in karst environment in Gunung Kidul, Yogyakarta, Indonesia - MAIZER SAID NAHDI; ARDYAN PRAMUDYA KURNIAWAN (Smujo International, 2019)
Abstract. Nahdi MS, Kurniawan AP. 2019. Ethnobotanical study of medicinal plants in karst environment in Gunung Kidul, Yogyakarta, Indonesia. Nusantara Bioscience 11: 133-141. The use of traditional medicinal plants has been a culture of the people in Yogyakarta including in Gunung Kidul District. This research aims to reveal information on medicinal plants in karst environment in Gunung Kidul, Yogyakarta, Indonesia by focusing on how medicinal plants are used, managed and inherited by the community. The research was conducted in Planjan Village and Giricahyo Village in Gunung Kidul District from June to September 2018. The method used in collecting data was exploratory survey and Participatory Rural Appraisal. Data of community knowledge and uses of medicinal plants were obtained through in-depth interview and structured interview. The identification of species was applied to every plant used. The study found that there are 46 species from 26 families used by the people in the two villages for medical treatments with the largest number of species is from Zingiberaceae family, followed by Fabaceae and Rutaceae. The medicinal plants are mostly packaged into six herbal medicinal plants called jamu beras kencur, kunir asem, paitan, kebyokan (uyup uyup), sirih and temu lawak with different compositions and efficacies. The result showed that people's knowledge about medicinal plants is obtained from elders who have a long experience in making concoction and trading the medicinal plants as traditional herbal medicine. In addition, the people are also obtained additional knowledge from any sources to make the medical plants to have economic value to improve their welfare. Most of the medicinal plants are obtained from the outside of the villages since it is impossible to cultivate in karst soils. Thus, the study is expected to help develop the local potential of medicinal plants to become more modern, can support the conservation of local wisdom and plant biodiversity, as well as be used as a source of material for developing national database on medicinal plant and its usage.